2017
DOI: 10.7287/peerj.preprints.3171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The evolutionary history of plant T2/S-type ribonucleases

Abstract: A growing number of T2/S-RNases are being discovered in plant genomes. Members of this protein family have a variety of known functions, but the vast majority are still uncharacterized. We present data and analyses of phylogenetic relationships among T2/SRNases, and pay special attention to the group that contains the female component of the most widespread system of self-incompatibility in flowering plants. The returned emphasis on the initially identified component of this mechanism yields important conjectu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…According to the classification of the T2 RNase gene family by Igic and Kohn (2001), S-RNases are included in the Class III cluster. The proteins coded by Class III T2 RNases have basic isoelectric points (pI), while most T2 RNases are acidic (Irie, 1999;Ramanauskas and Igic, 2017). Ramanauskas and Igic (2017) did an analysis using a large dataset of T2 RNase genes including S-RNases and revealed that the median predicted pI value in Class I proteins was 5.04, 5.90 in Class II, and was more basic in Class III; the median pI of non-S-RNases was 8.56 and that of S-RNase was 9.18.…”
Section: Molecular Weight and Isoelectric Pointmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the classification of the T2 RNase gene family by Igic and Kohn (2001), S-RNases are included in the Class III cluster. The proteins coded by Class III T2 RNases have basic isoelectric points (pI), while most T2 RNases are acidic (Irie, 1999;Ramanauskas and Igic, 2017). Ramanauskas and Igic (2017) did an analysis using a large dataset of T2 RNase genes including S-RNases and revealed that the median predicted pI value in Class I proteins was 5.04, 5.90 in Class II, and was more basic in Class III; the median pI of non-S-RNases was 8.56 and that of S-RNase was 9.18.…”
Section: Molecular Weight and Isoelectric Pointmentioning
confidence: 99%
“…The proteins coded by Class III T2 RNases have basic isoelectric points (pI), while most T2 RNases are acidic (Irie, 1999;Ramanauskas and Igic, 2017). Ramanauskas and Igic (2017) did an analysis using a large dataset of T2 RNase genes including S-RNases and revealed that the median predicted pI value in Class I proteins was 5.04, 5.90 in Class II, and was more basic in Class III; the median pI of non-S-RNases was 8.56 and that of S-RNase was 9.18. The pI appears to be significantly correlated with S-RNase function, although the functional causes of the association of protein pI values are unclear (Ramanauskas and Igic, 2017).…”
Section: Molecular Weight and Isoelectric Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…These RNases have been classified based on their distribution, pH, and base specificity into three different families: RNase A, RNase T1, and RNase T2 (Luhtala and Parker, 2010). RNase T2 family members are widely distributed, have been identified in various organisms, and are most diverse in plants (MacIntosh et al , 2010; MacIntosh, 2011; Ramanauskas and Igic, 2017). Most of the RNase T2 family proteins are either secreted or targeted to cellular compartments of the secretory pathway, such as the endoplasmic reticulum, vacuoles or lysosomes and act at acidic pH with nonspecificity in vitro for base cleavage (Irie, 1999; Deshpande and Shankar, 2002; MacIntosh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Growth inhibitor (protein complex) in the SSI system is activated at the stigma, when pollen grains and the pistil have matching monomers, which inhibit pollen germination (Lewis, Crowe, 1958;Knox, Heslop-Harrison, 1970;Foote et al, 1994;Chantha et al, 2013). According to the recent data, the GSI system in a number of species is based on recognizing specific ribonuclease (S-RNase) in the diploid tissue of the pistil splitting the stored rRNA of its own pollen grains (pollen tube growth is terminated) and S-related F-box proteins of the male haploid capable of inactivating a subset of S-RNase alleles, except for their allele relative (Entani et al, 2003;Yamane et al, 2003;Kubo et al, 2010;Ramanauskas, Igić, 2017;Chen et al, 2018). The SI system in beet plants is controlled by four S-loci, while having a gametophytic incompatibility type, but it still remains understudied at the molecular level (Lundqvist et al, 1973;Zhuzhzhalova, 2010).…”
Section: Introductionmentioning
confidence: 99%